On-line recognition of connected handwriting - Ford, David Malcolm (1991)
Computer technology has rapidly improved over the last few years, with more powerful machines becoming ever smaller and cheaper. The latest growth area is in portable personal computers, providing powerful facilities to the mobile business person. Alongside this development has been the vast improvement to the human computer interface, allowing noncomputer- literate users access to computing facilities. These two aspects are now being combined into a portable computer that can be operated with a stylus, without the need for a keyboard. Handwriting is the obvious method for entering data and cursive script recognition research aims to comprehend unconstrained, natural handwriting.